PHENOMENOLOGY STUDY: THE INTERPRETATING EXPERIENCE OF EX-PRISIONERS OF NARCOTICS ABUSER WHEN RETURNING TO THE COMMUNITY IN KABUPATEN KEDIRI - Bambang Wiseno; Indah Winarni; Fransiska Imavike Fevriasanty (NurseLine Journal, 2017)
Criminality is a serious problem having not been saved up to now. Narcotics cases are increasing every year and most of them done by the same person. This recurrent criminality is happened because of both the difficulty of getting on employment access and the lack of moral support from the community. Nursing as a professional job in healthcare especially Psychiatric Nursing is obliged to assist people with psychosocial problems including ex-prisoners of narcotics abuser. They return to the community with a lot of meaningful experiences and problems with no other people have. The purpose of this study was to discover the meaning of their experience when returning to their society. With qualitative research of interpretive phenomenology approach, in-depth-interview was done for six ex-prisoners of narcotics abusers as participants selected by purposive sampling method. The study was conducted in June 2017 in Kabupaten Kediri. Interpretative Phenomenology Analysis (IPA) was used to analyze the data and found 8 themes; guilty feeling to the family, leaving fate in life, getting moral support to improve their life better, getting ashamed for what they have ever done, feeling unworthy in the community, being given to do better, feeling not given the opportunity to do better, and not having a desire to the narcotics. From all these themes, it can be concluded that the shame and guilty feeling causes them to fate in life. The support of the community and a chance to better makes a strong intention to leave narcotics. They must have a tough struggle to gain a better life when returning to their community.